1997
DOI: 10.1172/jci119120
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea as a cause of systemic hypertension. Evidence from a canine model.

Abstract: Several epidemiological studies have identified obstructive sleep apnea (OSA) as a risk factor for systemic hypertension, but a direct etiologic link between the two disorders has not been established definitively. Furthermore, the specific physiological mechanisms underlying the association between OSA and systemic hypertension have not been identified. The purpose of this study was to systematically examine the effects of OSA on daytime and nighttime blood pressure (BP). We induced OSA in four dogs by interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
310
4
19

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(352 citation statements)
references
References 24 publications
11
310
4
19
Order By: Relevance
“…The hypertensive effect of chronic intermittent hypoxia outlasts hypoxemia in animal models. [4,5] Morgan et al demonstrated in healthy volunteers that hypoxic hypercapnia leads to a protracted increase in MSA, whereas hyperoxic hypercapnia only transiently increases sympathetic activity indicating that hypoxemia is responsible for the effect. [40] Chronic intermittent hypoxia has thus clinically relevant prolonged effects on blood pressure in animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypertensive effect of chronic intermittent hypoxia outlasts hypoxemia in animal models. [4,5] Morgan et al demonstrated in healthy volunteers that hypoxic hypercapnia leads to a protracted increase in MSA, whereas hyperoxic hypercapnia only transiently increases sympathetic activity indicating that hypoxemia is responsible for the effect. [40] Chronic intermittent hypoxia has thus clinically relevant prolonged effects on blood pressure in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In dogs, hypoxic episodes due to repetitive airway obstruction during sleep resulted in acute transient increases in nighttime blood pressure and eventually provoked a sustained daytime hypertension. [5] It is likely that the same mechanisms are valid in humans too, since obstructive sleep apnea leads to increased SNS activity and increased daytime blood pressure. [6][7][8] Obstructive breathing disorders are associated with cardiovascular diseases such as hypertension, [9][10][11] myocardial infarction, [12] stroke, [13] and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…About 60% of OSA-patients develop systemic hypertension 22 , even in the absence of any other risk factors when including both clinical and masked hypertension 4,23 . Using animal models 15,24 and also applying IH in healthy humans 25 suggest that IH is a major factor determining blood pressure increase. We have previously shown in C57BL6 mice that blood pressure surges appear at each hypoxic episode, and are associated with increased sympathetic activation 14 .…”
Section: Blood Pressure Alterations Due To Ihmentioning
confidence: 99%
“…[4][5][6][7] Their underlying pathological mechanisms include recurrent intermittent hypoxemia and increased sympathetic activity, primarily at the termination of the apneic events. 8,9 In a previous study, 10 our group showed that OSAS is also associated with ED in a dose-related fashion.…”
Section: Introductionmentioning
confidence: 99%